Development of card catalog media for early reading ability of students with mild intellectual disability - Nur Amriani; Syamsuddin Syamsuddin; Purwaka Hadi (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2022)
This study aims to (1) describe the need for media, (2) describe the prototype of the card catalog media, (3) investigate the validity and practicality of the card catalog media used to increase early reading ability of students with mild intellectual disability. This study used research and development method with the research stages developed by Borg & Gall. The data of this study were collected through interviews, questionnaires, and validation instruments. The analysis was performed using the descriptive quantitative analysis with the percentage technique. Results showed that (1) the card catalog media was much needed by teachers and students with mild intellectual disability to improve early reading ability in students at SLBN (State Special Education School) Lutang Majene; (2) the prototype of the media that had been developed consisted of cards, equipped with drawers to store the cards; each card was in various colors and contained pictures, letters, syllables, and words; and (3) through restricted testing, the card catalog media was considered very valid, practical and feasible to be used in early reading activities for students with mild intellectual disability.